Demoralisation in cancer patients: the association with distress, depression and positive emotion - Chin, HL; Ng, CG; Thong, Kai Shin; Seed, HF; Aili H (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Cancer patients experience a high level of distress and depression. The understanding of its psychological correlates such as demoralisation and positive emotion helps in the management of these conditions. The study objectives are to examine the correlation between demoralisation and positive emotion, defined as discrete pleasant emotions, such as joy, pride, contentment or love, with depression and distress in cancer patients. The sociodemographic and clinical associated factors are also studied. This cross-sectional study recruited 178 cancer patients from a local university hospital. They were assessed using the Malay versions of the Demoralization Scales (DS-M), Positive Emotion Rating Scale (PERS), Centre for Epidemiologic Studies Depression (CESD) Scale, and Distress Thermometer. The mean age of the subjects was 53.6 + 16.51 years old, with 24% of them were in the advanced stage of cancer. Almost 38% of the subject were demoralised. Of them, 61.2% were depressed, 52.2% had low positive emotion, and 68.7% were distressed. Demoralisation was positively correlated with depression (r=0.78, p<0.01) and distress level (r=0.64, p<0.01) but negatively correlated with positive emotion (r=-0.69, p<0.01). In conclusion, demoralisation was highly prevalent and strongly associated with depression and distress in cancer patients. Assessment and early detection of demoralisation among cancer patients should receive more attention. Future studies on the management of this condition are needed.